A brief review of features of copper indium disulphide (CuInS2) nanomaterials for quantum dot solar cells - Garg, Nitya (جامعة الوادي Université ofEl-Oued, 2023)
Copper indium disulphide CuInS2 (CIS) is found to be an interesting nanomaterial belong to group I-III-V for quantum dot solar cell (QDSCs) application due to low toxicity, multiple exciton generation effect, high light absorption in the visible spectral range, appropriate band gap that coordinate well with the solar spectrum, unusual radiation tolerance, noticeable defect tolerance and low cost. Properties of this material that makes it important for use in quantum dot solar cell is also discussed in this paper. This paper summarizes the research going on in the field of synthesis of CuInS2 nanomaterials reported by different authors across the globe. Optical and photovoltaic properties of reviewed CIS QDSCs is also highlighted in this paper.
Article
Keywords: Nanomaterials; Copper indium disulphide; Quantum dot solar cell; Synthesis techniques; Photovoltaic properties.